Notes on the genus Petascelis Signoret and description of one new species (Hemiptera: Heteroptera: Coreidae: Coreinae: Petascelini) - Brailovsky, Harry (Zootaxa, 2008)
A new species of the genus Petascelis belonging to the coreid tribe Petascelini is described from Tanzania under the name P. inconditus n.sp. Redescription of the genus, diagnoses for males and females as well as illustrations, new distributional records, and a key to all Petascelis taxa are provided.